Beyond resistance: Geographies of divergent more-than-human conduct in robotic milking. Issue 104 (August 2019) - Bear, Christopher; Holloway, Lewis
Highlights: Human-cow-robot relations around Automated Milking Systems can be dissonant. These relations can be analysed through the concept of divergent conduct. Divergent conduct highlights that actors' conduct can follow multiple trajectories. These trajectories co-constitute topological and topographical spatialities. Abstract: This paper begins to develop a terminology for discussing less-than-convivial more-than-human entanglements. The paper reviews existing work on such relations, showing how they tend to have been conceptualised in terms of animal transgression and resistance. It then develops critiques of these terms, focusing on their problematic representations of animals' actions and subjectivities, and engaging with arguments that non-living nonhumans also need to be considered in conceptualisations of problematic more-than-human situations. Drawing on empirical material from research into automated (or robotic) milking systems (AMS), and the associated relations between machines, humans and cows in specific places, the paper proposes and outlines the concept of divergent conduct. It argues that this is a way of exploring how heterogeneous entities co-produce activity which is likely to differ from accounts of trouble-free introductions of technologies and practices. The concept draws together an emphasis on the 'lively' nature of machines with a focus on the agency of nonhuman animals and the topological relationships involved in attempts to establish AMS in UK dairy farming. It suggests that the characteristics and capacities of heterogeneous entities make multiple and relational differences to situations. As such, the concept emphasises the constitution of AMS in relation to multiple human and nonhuman requirements, and their related conducts, which may pull in different directions. The paper argues that divergent conduct provides a way of exploring problematic and politicised entanglements in which inequalities of power can be many-layered and intersectional.